THE MARKETING OF SOCIAL ENTERPRISES: Understanding the concepts of marketing and market orientation of social enterprises within the context of Pakistani market - Siddique, Muhammad (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The concepts of social entrepreneurship and social enterprises have been extensively discussed in the previous two decades, yet the topic is still not matured yet. Most of the available literature is focused on defining these terms. Similarly, limited number of authors has discussed the marketing function of these enterprises or how marketing is interpreted in social entrepreneurship models. However, there is a plethora of literature on marketing entailing many different theories, amongst which the newest one is the “market orientation concept”. Market orientation is a mix of customer orientation, competitor orientation and inter-functional coordination suggesting marketing to be a part of the business philosophy. This study focuses on the marketing and market orientation of social enterprises while giving an overview of the literature of marketing and market orientation in social enterprises. This study aims to provide two basic questions, 1) what is the literature on marketing and market orientation of social enterprises while explaining the literature of social enterprises in Pakistan and 2) how these concepts are interpreted in social enterprises in Pakistani market. Key features of research methodology include case study approach while conducting thematic analysis using thematic networks. The results indicate that only a limited number of authors have discussed market orientation concept in social enterprises. The results from the interview data indicate the usage of marketing by a firm unconsciously without a specific marketing department. In addition to that, it has been found that in social enterprise world competition is tackled through a win-win approach with a view that many enterprises working for society improve the society which is the basic mission of any social enterprise. The data also showed that in Pakistani market, social enterprise concept is not legally used yet, which allows for more room for innovation. This study intends to give a new perspective to the theorists to use market orientation concept in social enterprises and also to managers to use marketing as their business philosophy in order to satisfy the stakeholders for better delivery of their businesses and as well for social good.